The prevalence of asymptomatic microscopic hematuria in primary school children of Bushehr port and Kharg Island - Khadijeh Ghasemi (Iranian South Medical Journal, 2004)
Asymptomatic hematuria is seen in 0.5-2% of school age children. Screening for proteinuria and hematuria is important in the prevention of chronic renal disease. In order to reveal the prevalence of asymptomatic hematuria, 2047 primary school children of Bushehr port and Kharg Island were chosen by multiple cluster sampling method. The screened children with positive protein or blood by dipstick were re-examined 2 weeks later. In the second phase 10 cc of urine of each student who had >= 1+ blood and/or >=2 + protein was centrifuged and examined by microscope. The prevalence of isolated microscopic hematuria in the first phase was 5.91% and it was decreased to 2.1% in the second phase. The prevalence of isolated microscopic hematuria was 1.5% (1.74 for males & 1.27 for females) and 3.4% (1.45 for males & 5.65 for females) in Bushehr port and Kharg Island, respectively. In conclusion, the prevalence of isolated microscopic hematuria in Bushehr port was the same as the other parts of the world, however the prevalence of isolated hematuria was high in Kharg Island which needs further investigations.